The Efficacy of Triamcinolone Acetonide in Keloid Treatment: A Systematic Review and Meta-analysis - Wong, Thian-Sze; Li, John Zeng-Hong; Chen, Siqi; Chan, Jimmy Yu-Wai; Gao, Wei (Frontiers in Medicine, 2016)
Keloid is a cutaneous dermal outgrowth resulting from uncontrolled deposition of collagen and glycosaminoglycan around the wound. The uncontrolled and persistent growth of keloids scar will result in cosmetic disfigurement, functional impairment and affect the quality of life. Triamcinolone acetonide (TAC) is traditionally employed in treating keloid scars. In the present study, we aim to evaluate the effectiveness of TAC and compare it with other common therapy employed in keloid treatment. Only randomized controlled trial (RCT) and controlled trial (CT) were included. Inverse variance risk ratio (RR), weighted mean difference (WMD) and corresponding 95% confidence intervals (CI) were calculated to evaluate the effect of intervention. Meta-analysis indicated that TAC treatment significantly reduced the size of keloid compared to untreated control. Reduction in size was statistically different in favor of TAC compared to silicone gel sheet. Significant difference in favor of TAC was observed compared with verapamil in term of vascularity and scar pliability. TAC treatment was more effective in reducing scar thickness in comparison with cryotherapy. However, the current meta-analysis has several limitations. Only a limited number of trials with the same comparison are available. Most trials recruited a small number of patients and used inconsistent outcome assessment. Most trials did not provide detail information on allocation concealment and blinding. Therefore, further evaluation in multi-center randomized controlled trials with consistent comparisons and outcome measurements are warrant to reach a consensus on the selection between TAC and different treatment modalities.